2011
DOI: 10.1038/onc.2011.161
|View full text |Cite
|
Sign up to set email alerts
|

A novel interplay between oncogenic PFTK1 protein kinase and tumor suppressor TAGLN2 in the control of liver cancer cell motility

Abstract: The PFTK1 gene encodes a cdc2-related serine/threonine protein kinase that has been shown to confer cell migratory properties in hepatocellular carcinoma (HCC). However, the prognostic value and biological mechanism by which PFTK1 promotes HCC motility remain largely unknown. Here, we showed from tissue microarray that common upregulations of PFTK1 in primary HCC tumors (n ¼ 133/180) correlated significantly with early age onset (p40 years), advance tumor grading and presence of microvascular invasion (Pp0.05)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 29 publications
4
63
1
Order By: Relevance
“…Interestingly, TAGLN2 is a known tumor suppressor, yet its upregulated expression is associated with increased metastasis, and worse patient prognosis. This outcome may be related to findings in HCC where phosphorylation of TAGLN2 by PFTK1 (an oncogenic serine/threonine protein kinase) inactivates its actin-binding function, abrogating its suppression of cell motility [139] . Fur thermore, in mouse metaphase I oocytes after IGF1 treatment, miRNA133b was upregulated more than 30fold and target TAGLN2 was downregulated, stimulating growth and maturation of the oocytes [140] .…”
Section: Cell Factors Deregulated In Cancer By Myomirsmentioning
confidence: 64%
“…Interestingly, TAGLN2 is a known tumor suppressor, yet its upregulated expression is associated with increased metastasis, and worse patient prognosis. This outcome may be related to findings in HCC where phosphorylation of TAGLN2 by PFTK1 (an oncogenic serine/threonine protein kinase) inactivates its actin-binding function, abrogating its suppression of cell motility [139] . Fur thermore, in mouse metaphase I oocytes after IGF1 treatment, miRNA133b was upregulated more than 30fold and target TAGLN2 was downregulated, stimulating growth and maturation of the oocytes [140] .…”
Section: Cell Factors Deregulated In Cancer By Myomirsmentioning
confidence: 64%
“…Gene set enrichment analysis 8 also indicated that the TEAD4-regulated transcriptome in CRC cells is rich in mesenchymal-related genes and in genes participating in cell migration (Figure 3c). Among the genes identified by the microarray analysis as TEAD4 targets, LOX, 9 DKK1 10 CDK14, 11 and MSN 12 have previously been implicated in cancer metastasis. As assessed by real-time PCR, these genes were all downregulated after TEAD4 knockdown (Figure 3d).…”
Section: Tead4 Knockdown In Mesenchymal-like Crc Cells Induces Mesencmentioning
confidence: 99%
“…Cdk10 is a major determinant of resistance to endocrine therapy for breast cancer [62], and inhibition of Cdk12 confers sensitivity to inhibitors of poly (ADP-ribose) polymerases PARP1 and PARP2 [63]. Cdk14 confers motility advantages and metastatic potential in hepatocellular carcinoma motility and metastasis [64,65]. Finally, as indicated above, cyclin Y kinases regulate the Wnt pathway [31], providing new therapeutic opportunities that are yet to be explored.…”
Section: Frontiersmentioning
confidence: 99%